Unusual Presentation of Adenomatoid Odontogenic Tumor - A Report of Two Cases - J Rema; Anita Balan; Deepa Das (Wolters Kluwer Medknow Publications, 2004)
Adenomatoid Odontogenic Tumor (AOT) is a relatively uncommon odontogenic tumor Characterized by the formation of duct like structures by the epithelial component. According to the reports most of the cases occur in the second and third decades of life with only a few cases occurring in people over 50 years. Most often this tumor occurs in the maxillary anterior region with few cases occurring distal to premolar region. The most common radiographic appearance of adenomatoid odontogenic tumor is a sharply circumscribed unilocular radiolucecy associated with the crown of an unerupted maxillary anterior tooth especially canine. Radioopacities were reported in two thirds of the cases. Here we report two unusual presentations of adenomatoid odontogenic tumor. These cases are of particular interest because the site of occurrence, size of lesion and radiographic findings were not typical of adenomatoid odontogenic tumor.